Chapter 13. Special Populations (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
AuthorMr. Vamsi Ch, PharmD InternDepartment of Pharmacy Practice, Koringa College of Pharmacy, Korangi, Andhra Pradesh, IndiaAbstractPharmacological management in special populations requires modified therapeutic approaches based on physiological variations and specific risk factors. Pediatric patient care incorporates age-specific dosing calculations, formulation considerations, and developmental pharmacokinetic parameters. Geriatric pharmacotherapy emphasizes medication appropriateness assessment, polypharmacy management, and adverse effect prevention using validated screening tools. Pregnancy and lactation drug selection follows risk categorization systems with evaluation of maternal benefit versus fetal risk ratios. Organ dysfunction necessitates systematic dose adjustments and alternative drug selection based on specific elimination pathways and metabolic considerations. Genetic variation impact on drug response requires pharmacogenetic testing protocols and dose modification strategies for identified polymorphisms. Treatment approaches incorporate population-specific monitoring parameters, adverse effect profiles, and therapeutic response indicators with regular reassessment of risk-benefit ratiosKeywords: Special populations, Pediatric dosing, Geriatric pharmacotherapy, Pregnancy medications, PharmacogeneticsVIEW PDF